Global diffusion flame extinction strain rate experiments of single large hydrocarbon fuels - Jadhav, Anish, author; Windom, Bret C., author (Colorado State University. Libraries, 2017)
An experimental validation study of the flame extinction characteristics of large hydrocarbon fuels is carried out. A counterflow flame burner combined with a liquid fuel vaporization system is utilized at a reduced pressure of 0.84 atm to measure the diffusion flame global extinction strain rate of liquid fuels as a function of fuel dilution. A numerical study is also employed using CHEMKIN to calculate the global extinction strain rate of hydrocarbon fuels, including n-heptane, n-decane, and toluene. Flame extinction measurements of the blended fuels are compared to global flame extinction predictions using a previously published radical index methodology.
143 - Anish Sharad Jadhav
Global extinction strain rate experiments of single large hydrocarbon fuels
Keywords: extinction strain rate; CHEMKIN; hydrocarbon fuel